Microbiological Quality of Pig Carcasses in a Slaughterhouse under Risk-Based Inspection System - Luciana Giacometti Cavalheiro; Luisa Aneiros Gené; Arlei Coldebella; Jalusa Deon Kich; Vera Letticie de Azevedo Ruiz (Foods, 2022)
Meat product inspection is one of the procedures adopted more than a century ago to guarantee food quality and safety for consumption. Due to technology and regulation advancement for farming and slaughtering pigs, a change in zoonotic profile attributed to pork has been identified. Thus, a global movement began to establish inspection parameters based on epidemiological risk profiles, culminating in the publication of a new regulation in Brazil in 2018. This normative instruction establishes that slaughterhouses under federal inspection must implement risk-based inspection until 2028. Changes in the inspection system can generate questions and objections on the part of customers and consumer markets. In order to assess microbiological contamination when adopting a risk-based inspection system, the occurrence of Salmonella spp. and the quantification of Enterobacteriaceae and mesophilic aerobic counts were compared in pig carcasses slaughtered under traditional and risk-based inspection systems. A statistical significance reduction was identified regarding the quantification of Enterobacteriaceae (log −0.18 to −1.61 CFU/cm2) and mesophilic aerobic counts (log 4.60 to 3.49 CFU/cm2). The occurrence of Salmonella spp. did not show a significant difference (4% to 5.3%). The results allowed us to conclude that adopting risk-based inspection systems improves food safety through Enterobacteriaceae and mesophilic aerobic counts reduction.